The Impact of Rotary Blood Pump in Conjunction with Mechanical Ventilation on Ventricular Energetic Parameters - De Lazzari, C.; Darowski, M.; Ferrari, G.; Pisanelli, D. M.; Tosti, G. (Methods of Information in Medicine, 2006)
Objectives: Aim of this work is to study the impact of left ventricular rotary blood pump assistance, on energetic variables, when mechanical ventilation (MV) of the lungs is applied.Methods: Computer simulation was used to perform this study. Lumped parameter models reproduce the circulatory system. Variable elastance models reproduce the Starling’s law of the heart for each ventricle. After the reproduction of ischemic heart disease left ventricular assistance was applied using a model of rotary blood pump. The pump speed was changed in steps and was assumed to be constant during each step. The influence of mechanical ventilation was introduced by different values of positive mean thoracic pressure.Results: The increase of the rotational speed has a significant influence on some ventricular energetic variables. In fact it decreased left ventricular external work, left and right ventricular pressure-volume area and the left ventricular efficiency. Finally, it increased the right ventricular efficiency but had no influence on the right ventricular external work. The increase of thoracic pressure from –2 to +5 mmHg caused a significant decrease of external work, pressure-volume area (right ventricular pressure-volume area dropped up to 50%) and an increase of right ventricular efficiency (by 40%) while left ventricular efficiency remained almost stable.Conclusions: Numerical simulation is a very suitable tool to predict changes of not easily measurable parameters such as energetic ventricular variables when mechanical assistance of heart and/or lungs is applied independently or simultaneously.
Keywords: Mock circulatory system; mechanical ventilation; rotary blood pump; numerical simulation; energetic variables